(untitled) (NAU Journal of Technology and Vocational Education, 2024)
This study ascertained human relation skills needed by business education graduates for sustainability of SMEs in Imo State. One research question guided the study while two null hypotheses were tested. The descriptive survey research design was adopted for the study. The sstudy was carried out in Imo State. The population of this study comprised 130 SMEs registered with the Imo State chamber of Commerce and Industry as at 2019. The entire population of 130 registered SMEs was used for the study since the size is considered manageable. Data for the study was collected using a validated research questionnaire. Cronbach Alpha was used to determine the internal consistency of the instrument which yielded a reliability coefficient value of 0.81. Arithmetic mean and standard deviation was used to answer research questions and determine the homogeneity or otherwise of the respondents’ ratings. The t-test and Analysis of Variance (ANOVA) was used to test the null hypotheses. The findings of the study revealed among others that applying positive reinforcement when relating with others, developing good customer orientation for effective operation, persuading customers and stakeholder as expected were highly needed human relations skill. The finding also revealed that there was no significant difference in the mean responses of SME managers on human relation skills needed by business education graduates for sustainability of SMEs based on their years of experience. Based on the findings, it was recommended among others that business education graduates should attend more workshops, seminars, and conferences that emphasizes on the importance of human relations skills for sustainability of SMEs.